Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Open problems in ageing science: a roadmap for biogerontology - Angelo Talay; Aleksey V. Belikov; Paul Ka Po To; Hamid H. Alfatemi; Uri Alon; Joris Deelen; Collin Y. Ewald; David Gems; Vera Gorbunova; Jan Gruber; Sara Hägg; John Hemming; et al. (GeroScience, 2025)

Variations in vulnerability across aquifer layers in a heterogeneous aquifer system - Collins Kissi Asante-Sasu; Jon Turk; Seann McClure; Alexandra McLarty (Groundwater for Sustainable Development, 2025)

Green infrastructure impacts in winegrowing: A systematic map - Ebba Engström; Robert Fish; Caroline Howe; Catherine Matilda Collins; Benjamin J. Roberts; Samuel Watkins; Alexandra Collins (Agriculture, Ecosystems & Environment, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Dog swimming and ectoparasiticide water contamination in urban conservation areas: A case study on Hampstead Heath, London - Lauren E. Yoder; Melanie Egli; Alexandra K. Richardson; Adrian Brooker; Rosemary Perkins; C.M. Tilly Collins; Jacqueline M. Cardwell; Leon P. Barron; Jeff Waage (Science of The Total Environment, 2024)

A global systematic review of the cultural ecosystem services provided by wetlands - Kevin A. Wood; Lucy L. Jupe; Francisca C. Aguiar; Alexandra M. Collins; Scott J. Davidson; Will Freeman; Liam Kirkpatrick; Tatiana Lobato-de Magalhães; Emma McKinley; Ana Nuno; Jordi F. Pagès; Antonella Petruzzella; et al. (Ecosystem Services, 2024)

Managing offshore multi-use settings: Use of conceptual mapping to reduce uncertainty of co-locating seaweed aquaculture and wind farms - Ryan O'Shea; Elisa Capuzzo; Victoria Hemming; Gretchen Grebe; Rick Stafford; Sander W.K. van den Burg; Daniel Wood; Gordon Watson; Victoria Wells; Teresa Johnson; Stefan Erbs; Jaap W. van Hal; et al. (Journal of Environmental Management, 2024)

Trends and patterns in the application of co-production, co-creation, and co-design methods in studies of green spaces: A systematic review - Ngoc Thuy Nguyen; Alexandra Collins; Catherine Matilda Collins (Environmental Science & Policy, 2024)

The Nature Smart Cities business model: A rapid decision-support and scenario analysis tool to reveal the multi-benefits of green infrastructure investments - Wito Van Oijstaeijen; Maíra Finizola e Silva; Phil Back; Alexandra Collins; Kris Verheyen; Robbe De Beelde; Jan Cools; Steven Van Passel (Urban Forestry & Urban Greening, 2023)

Consensus Recommendations for Clinical Outcome Assessments and Registry Development in Ataxias: Ataxia Global Initiative (AGI) Working Group Expert Guidance - Thomas Klockgether; Matthis Synofzik; Saud Alhusaini; Mathieu Anheim; Irina Antonijevic; Tee Ashizawa; Luis Bataller; Mélanie Berard; Enrico Bertini; Sylvia Boesch; Pedro Braga-Neto; Emanuel Cassou; et al. (The Cerebellum, 2023)
To accelerate and facilitate clinical trials, the Ataxia Global Initiative (AGI) was established as a worldwide research platform for trial readiness in ataxias. One of AGI’s major goals is the harmonization and standardization of outcome assessments. Clinical outcome assessments (COAs) that describe or reflect how a patient feels or functions are indispensable for clinical trials, but similarly important for observational studies and in routine patient care. The AGI working group on COAs has defined a set of data including a graded catalog of COAs that are recommended as a standard for future assessment and sharing of clinical data and joint clinical studies. Two datasets were defined: a mandatory dataset (minimal dataset) that can ideally be obtained during a routine clinical consultation and a more demanding extended dataset that is useful for research purposes. In the future, the currently most widely used clinician-reported outcome measure (ClinRO) in ataxia, the scale for the assessment and rating of ataxia (SARA), should be developed into a generally accepted instrument that can be used in upcoming clinical trials. Furthermore, there is an urgent need (i) to obtain more data on ataxia-specific, patient-reported outcome measures (PROs), (ii) to demonstrate and optimize sensitivity to change of many COAs, and (iii) to establish methods and evidence of anchoring change in COAs in patient meaningfulness, e.g., by determining patient-derived minimally meaningful thresholds of change.

Genotoxic effects of occupational exposure to glass fibres - A human biomonitoring study - Marcello Ceppi; Bozena Smolkova; Marta Staruchova; Alena Kazimirova; Magdalena Barancokova; Katarina Volkovova; Andrew Collins; Anton Kocan; Zuzana Dzupinkova; Alexandra Horska; Verona Buocikova; Jana Tulinska; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Snapshot transient absorption spectroscopy: toward in vivo investigations of nonphotochemical quenching mechanisms - Soomin Park; Collin J. Steen; Alexandra L. Fischer; Graham R. Fleming (Photosynthesis Research, 2019)

Ecological assessments of surface water bodies at the river basin level: a case study from England - Alexandra Collins; Nikolaos Voulvoulis (Environmental Monitoring and Assessment, 2014)

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

Dissecting impact of plant invaders: Do invaders behave differently in the new range? - Yan Sun; Alexandra R. Collins; Urs Schaffner; Heinz Müller-Schärer (Ecology, 2013)
Knowledge from basic plant ecology suggests that impact of one plant species on another is driven by either competition for the same limiting resources, or by unique plant traits. These processes might be context specific, explaining a differential impact of exotic plant invaders in the native vs. introduced range. With the help of a conceptual framework, we aimed at identifying the relationship between invader biomass and impact in the invasive Centaurea stoebe by conducting pairwise competition experiments with 15 European (old) and 15 North American (new) neighboring species. Old neighbors grew larger and could use available soil moisture more efficiently for growth than new neighbors. Interestingly, biomass of C. stoebe explained a substantial amount of the variation in biomass of the coevolved neighbors, but not of the new “naïve” neighbors. Thus, impact in the home range appears to be driven by competition for the same limiting resources, but by other factors in the introduced range, possibly by exploitation of resources that are not used by the new neighbors or by interference competition. This distinction has important consequences for the management of invasive species, as in our study ecosystem recovery is less likely after simple biomass reduction.

Development and application of GIS datasets for assessing and managing coastal impacts and future change on the central coast of Western Australia - Alexandra Stevens; Lindsay Collins (Journal of Coastal Conservation, 2011)

Differential response to frequency-dependent interactions: an experimental test using genotypes of an invasive grass - Alexandra Collins; E. M. Hart; J. Molofsky (Oecologia, 2010)

Cogongrass ( Imperata cylindrica ), an Alien Invasive Grass, Reduces Survival and Productivity of an Establishing Pine Forest - Pedram Daneshgar; Shibu Jose; Alexandra Collins; Craig Ramsey (Forest Science, 2008)
A 27-month-long study was conducted to compare the impacts of Imperata cylindrica (L.) (Beauv.) and native vegetation competition on the productivity of Pinus taeda (L.) seedlings. In March 2003, 1-year-old pine seedlings were planted in the following treatments: vegetation free (VF), native competition (NC), and I. cylindrica (IC) competition. At the end of the study, only 26% of the IC seedlings survived, half of what was observed in the NC treatment. The IC seedlings had significantly smaller root collar diameter than the NC seedlings (P < 0.0001) after the first growing season and by the end of the third growing season the height and stem volume index were significantly less as well (P < 0.0001). After one full growing season, the NC and IC pine seedlings had 21 and 11.5% of the total biomass of the VF seedlings, respectively. After three growing seasons, the IC pine seedling total biomass was 2.4% of that of the VF seedlings and 18% of that of the NC seedlings (P < 0.0001). The greatest difference was in the pine needle biomass with the IC pine needle biomass being only 11% of that of the NC. During the first growing season, the IC pine seedlings maintained the lowest levels of light-saturated net photosynthesis and stomatal conductance. These results may be explained by reduced amounts of foliar nitrogen and water stress that result from I. cylindrica competition. The pines in the IC treatment had the lowest total foliar surface area and the lowest specific leaf area, which may explain the reduced productivity. Evidence from this study suggests that I. cylindrica competition significantly reduces the productivity and growth of P. taeda seedlings compared with that from native vegetation.